Risk navigation for Thinking and Working Politically: The work and disappearance of Sombath Somphone. (2nd December 2020) - Sims, Kearrin
Abstract: Motivation: On December 15, 2012 Sombath Somphone was abducted at a police checkpoint in his home city of Vientiane, the capital of Laos; his whereabouts remain unknown. This article considers his work and disappearance through the lens of Thinking and Working Politically (TWP) approaches to development. The article is supportive of TWP, but emphasizes the significant risks of politicized programming in authoritarian contexts. Purpose: By examining the case of Sombath Somphone, the article seeks to offer insights for safer, and more effective, TWP programming. It considers how specific events in authoritarian contexts can suddenly reposition development workers and/or organizations as political dissidents. Approaches and Methods: The argument draws on analysis of grey literature; conversational and observational knowledge accrued during 18 months of fieldwork in Laos between 2011 and 2018; on‐going formal and informal interviews with members of Laos' civil society sector; and extensive dialogue with Sombath Somphone's wife, Ng Shui Meng. Findings: The article identifies four key factors that contributed to the enforced disappearance of Sombath Somphone: international exposure; timing; particular elites; and strategies of oppression. It highlights the need for further consideration of how to anticipate and mitigate the dangers of politically oriented development work, as well as the different forms of risk experienced by local and international development actors working in authoritarian contexts. Policy Implications: TWP has much to offer to development practice, but its contributions should not threaten the safety of local development actors. More attention must be given to preventing and mitigating such risks.